AKTIVISME NON GOVERNMENT ORGANIZATION DALAM MENCIPTAKAN KESETARAAN GENDER (Studi Kasus Peran Econatural Society Dalam Pemberdayaan Perempuan) - Ema Angraeni; Kaslam Kaslam (SOSIORELIGIUS, 2021)
This paper aims to analyze the role of NGOs, especially the Econatural Society in empowering women. The type of research used is descriptive qualitative, which seeks to reveal a phenomenon that occurs in society with a descriptive approach. The data used comes from the results of interviews and direct observations made by the author at the location of the Econatural Society's activities. While the supporting data is taken from references such as journals, books and news on the website. As a result, the authors found the fact that the Econatural Society, as an independent institution and acts as a facilitator in empowerment in the community, has provided opportunities for women (especially housewives). They need life skills such as hydroponic plant cultivation, maggot cultivation, catfish cultivation using tarpaulins, by utilizing unused land in Makassar City. The Econatural Society fosters women so that they can generate and increase the income of housewives, on the other hand, these activities can be carried out easily because they do not require excessive time and energy. This proves that one of Econatural's roles is to empower women in the community to create gender equality and increase the income and economy of the surrounding community.